Repeated Administration of Clinical Doses of Tramadol and Tapentadol Causes Hepato- and Nephrotoxic Effects in Wistar Rats - Joana Barbosa; Juliana Faria; Fernanda Garcez; Sandra Leal; Luís Pedro Afonso; Ana Vanessa Nascimento; Roxana Moreira; Odília Queirós; Félix Carvalho; Ricardo Jorge Dinis-Oliveira (MDPI AG, 2020)
Tramadol and tapentadol are fully synthetic and extensively used analgesic opioids, presenting enhanced therapeutic and safety profiles as compared with their peers. However, reports of adverse reactions, intoxications and fatalities have been increasing. Information regarding the molecular, biochemical, and histological alterations underlying their toxicological potential is missing, particularly for tapentadol, owing to its more recent market authorization. Considering the paramount importance of liver and kidney for the metabolism and excretion of both opioids, these organs are especially susceptible to toxicological damage. In the present study, we aimed to characterize the putative hepatic and renal deleterious effects of repeated exposure to therapeutic doses of tramadol and tapentadol, using an in vivo animal model. Male Wistar rats were randomly divided into six experimental groups, composed of six animals each, which received daily single intraperitoneal injections of 10, 25 or 50 mg/kg tramadol or tapentadol (a low, standard analgesic dose, an intermediate dose and the maximum recommended daily dose, respectively). An additional control group was injected with normal saline. Following 14 consecutive days of administration, serum, urine and liver and kidney tissue samples were processed for biochemical, metabolic and histological analysis. Repeated administration of therapeutic doses of both opioids led to: (i) increased lipid and protein oxidation in liver and kidney, as well as to decreased total liver antioxidant capacity; (ii) decreased serum albumin, urea, butyrylcholinesterase and complement C3 and C4 levels, denoting liver synthesis impairment; (iii) elevated serum activity of liver enzymes, such as alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and γ-glutamyl transpeptidase, as well as lipid profile alterations, also reflecting hepatobiliary commitment; (iv) derangement of iron metabolism, as shown through increases in serum iron, ferritin, haptoglobin and heme oxygenase-1 levels. In turn, elevated serum cystatin C, decreased urine creatinine output and increased urine microalbumin levels were detected upon exposure to tapentadol only, while increased serum amylase and urine N-acetyl-β-D-glucosaminidase activities were observed for both opioids. Collectively, these results are compatible with kidney injury. Changes were also found in the expression levels of liver- and kidney-specific toxicity biomarker genes, upon exposure to tramadol and tapentadol, correlating well with alterations in lipid profile, iron metabolism and glomerular and tubular function. Histopathological analysis evidenced sinusoidal dilatation, microsteatosis, mononuclear cell infiltrates, glomerular and tubular disorganization, and increased Bowman's spaces. Although some findings are more pronounced upon tapentadol exposure, our study shows that, when compared with acute exposure, prolonged administration of both opioids smooths the differences between their toxicological effects, and that these occur at lower doses within the therapeutic range.